IMPLEMENTATION OF THE GREAT PARENTS SCHOOL PROGRAM IN STUNTING PREVENTION IN BEBEKAN VILLAGE, TAMAN DISTRICT - Arifin, Muhammad Zainul; Sukmana, Hendra (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study analyzes the implementation of the School of Great Parents (SOTH) Program, which aims to reduce stunting in Bebekan Village, Taman District, Sidoarjo Regency, and improve parents' knowledge and skills in caring for toddlers, particularly regarding stunting and pre-stunting. Method: The methodology used in this study is descriptive qualitative, referring to George C. Edward III's implementation theory, which focuses on four indicators: communication, resources, implementer attitudes, and bureaucratic structure, with data collected through interviews, observations, and documentation involving health cadres, Working Group 4, and mothers with toddlers. Result: The results show that program communication is running relatively well through socialization, human resources and existing facilities are adequate despite limited funds, implementers show high commitment even without incentives, and the bureaucratic structure follows established procedures. Novelty: The conclusion of this study emphasizes that SOTH plays a significant role in increasing parental awareness, but community participation and financial support need to be increased, highlighting the unique contribution of evaluating stunting prevention programs through the lens of internal implementation mechanisms at the village level.